Cleistothecia and Flag Shoots: Sources of Primary Inoculum for Grape Powdery Mildew in the Western Cape Province, South Africa - Halleen, F.; Holz, G. (South African Journal of Enology and Viticulture, 2017)
Little is known about the mode of survival and sources of primary inoculum of Uncinula necator, the causal pathogen of grapevine powdery mildew, in vineyards in the Western Cape province. A study was therefore undertaken to determine whether cleistothecia and flag shoots are formed on vines in local vineyards. Flag shoots were found shortly after budbreak in September 1997 in a Carignane vineyard near Somerset West. Cleistothecia were first observed during April to May 1996 on severely infected leaves from three vineyards in the main grapegrowing areas of Stellenbosch. This was the first report of cleistothecia and flag shoot formation in vineyards in the Western Cape province. Cleistothecia occurred in small numbers on leaves (1 - 10 per leaf) and all were immature. Cleistothecia were dispersed by late summer and autumn rains from leaves to bark of grapevines, where they overwinter. No conclusion could be made regarding the viability of cleistothecia. However, the characteristics of the first symptoms that developed on leaves, namely separate, individual lesions formed at random on first-formed leaves growing in close proximity to the bark, provided circumstantial evidence that cleistothecia are dispersed to the bark. Weather conditions suitable for release of ascospores from overwintered cleistothecia occurred frequently between budbreak and bloom in all the areas.